2021
DOI: 10.3389/fimmu.2021.772941
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Neuroimmune Interactions of TSLP and TRPV4 Play Pivotal Roles in Dry Skin-Induced Pruritus

Abstract: Dry skin is a symptom of skin barrier dysfunction that evokes pruritus; however, the cutaneous neuroimmune interactions underlying dry skin-induced pruritus remain unclear. Therefore, we aimed to elucidate the mechanisms underlying dry skin-induced pruritus. To this end, an acetone/ethanol/water (AEW)-induced mouse model of dry skin was used in this study. We observed that the production of thymic stromal lymphopoietin (TSLP) significantly increased in the keratinocytes of AEW mice. Importantly, treatment with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 34 publications
1
11
0
Order By: Relevance
“…For example, it was found that there are complex cutaneous neuroimmune interactions between TSLP cytokines and TRPV4 ion channel. 34 More importantly, dry skin induces overexpression of MrgprA3 as well as an increase in the percentage of MrgprA3 + sensory neurons. 11 We also observed that MrgprA3 is the most abundantly expressed itch-related gene in DRG neurons of mice treated with AEW.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it was found that there are complex cutaneous neuroimmune interactions between TSLP cytokines and TRPV4 ion channel. 34 More importantly, dry skin induces overexpression of MrgprA3 as well as an increase in the percentage of MrgprA3 + sensory neurons. 11 We also observed that MrgprA3 is the most abundantly expressed itch-related gene in DRG neurons of mice treated with AEW.…”
Section: Discussionmentioning
confidence: 99%
“…TSLP is released from keratinocytes in response to cutaneous pathogens, such as Staphylococcus aureus ( 66 ) and Malassezia yeasts ( 67 ), and environmental stimuli, such as ultraviolet radiation ( 68 ), mechanical injury ( 41 ), and air pollutants ( 69 ). The thermosensitive transient receptor potential channels TRPV3 and TRPV4 ( 70 , 71 ), pattern recognition receptor TLR3 ( 72 , 73 ), and PAR2 ( 38 , 74 ) are among the receptors that can sense the external stimuli and induce the production of TSLP in keratinocytes. Vitamin D3 also induces the expression of TSLP in keratinocytes, which leads to the development of an atopic dermatitis-like phenotype ( 75 ).…”
Section: Tslpmentioning
confidence: 99%
“…PAR2-triggered release of TSLP can stimulate sensory neurons to evoke the itch response in allergic diseases such as atopic dermatitis, in a TSLPR- and TRPA1-dependent manner ( 38 ). In addition, TRPV4 triggers TSLP release, which activates sensory neurons through TSLPR and TRPV4 in a dry skin-induced pruritus model ( 71 ). TSLP is found to be involved in the later phase of itch progression in allergic inflammation while neutrophil-derived CXCL10 drives itch in the acute phase, which is mediated through CXCR3 on sensory neurons ( 100 ).…”
Section: Tslpmentioning
confidence: 99%
“…TRPV4 has been found to mediate dry-skin-induced pruritis [ 193 ] and chronic pruritis [ 180 ]. Accordingly, in the latter investigation, TRPV4 expression was found to be significantly increased in skin biopsies from patients with chronic idiopathic pruritus compared to skin from healthy control subjects.…”
Section: The Endocannabinoid System In the Skinmentioning
confidence: 99%